2017
DOI: 10.1111/1460-6984.12362
|View full text |Cite
|
Sign up to set email alerts
|

Syntax and reading comprehension: a meta‐analysis of different spoken‐syntax assessments

Abstract: The results of this meta-analysis confirmed that the type of spoken-syntax assessment, whether norm-referenced or researcher-created, did not explain why some researchers reported that there were no significant differences between children with average and below-average reading comprehension, but the syntax construct, awareness or knowledge, did. Thus, when selecting how to measure syntax among school-age children, researchers and practitioners should evaluate whether they are measuring children's awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…Whereas a handful of meta‐analyses has investigated the relation between oral language and reading comprehension (e.g., Rogde, Hagen, Melby‐Lervåg, & Lervåg, 2019; Silverman et al, 2020), there has been only one published meta‐analysis on syntactic skills and reading comprehension. Brimo, Lund, and Sapp (2018) identified studies that compared syntactic skills of students with poor reading comprehension against those of typically developing students. Collating across the 14 studies identified, there was evidence of stronger performance on syntactic comprehension for students with good reading comprehension in comparison with those with poor reading comprehension; there were no such differences for syntactic awareness.…”
Section: Looking Ahead: Meta‐analysesmentioning
confidence: 99%
“…Whereas a handful of meta‐analyses has investigated the relation between oral language and reading comprehension (e.g., Rogde, Hagen, Melby‐Lervåg, & Lervåg, 2019; Silverman et al, 2020), there has been only one published meta‐analysis on syntactic skills and reading comprehension. Brimo, Lund, and Sapp (2018) identified studies that compared syntactic skills of students with poor reading comprehension against those of typically developing students. Collating across the 14 studies identified, there was evidence of stronger performance on syntactic comprehension for students with good reading comprehension in comparison with those with poor reading comprehension; there were no such differences for syntactic awareness.…”
Section: Looking Ahead: Meta‐analysesmentioning
confidence: 99%
“…Specifically, language skills, including phonological knowledge, morphological knowledge, vocabulary knowledge, and orthographic knowledge, are important word-level skills in the process of building surface structure (Ehri, 2014;Quinn et al, 2015;Xie and Wu, 2019;Liu and Liu, 2020). In the textbase representation process, the language skill of syntactic knowledge is essential as it helps readers to group words, trace the logical and semantic relations among linguistic constituents, and build initial propositions (So and Siegel, 1997;Cheung et al, 2007;Brimo et al, 2018;Simpson et al, 2020). In the situation model construction process, cognitive skills, such as comprehension monitoring and inference making, are necessary to detect internal and external inconsistences and draw inferences (Cain et al, 2004;Connor et al, 2015;Oakhill et al, 2015;Wong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Syntax is a language skill designated for supporting children's reading comprehension. Nevertheless, studies examining the children having average and below-average reading comprehension scores report inconsistent findings (Brimo et al, 2018). To the best of our knowledge, no Persian study has specifically investigated syntax comprehension of orphans.…”
Section: Discussionmentioning
confidence: 93%